Microstructure and Phase Transition of Ag50.5Cu33.3Sn16.2-xInx Alloys through Experimental Study and Thermodynamic Calculation - Qingsong Tong; Maohua Rong; Jiang Wang (Metals, 2023)
In this study, the solidified microstructure and phase transition temperatures of Ag50.5Cu33.3Sn16.2-xInx (x = 5.0, 6.6, 8.2, 9.1, 9.9, 10.7, 11.5, 12.3; at.%) alloys were investigated using a scanning electron microscope with energy dispersive spectrometer (SEM-EDS) and differential thermal analysis (DTA). The experimental microstructure of Ag50.5Cu33.3Sn16.2-xInx alloys demonstrates that the phase fraction of Fcc(Ag) phase increased gradually as the addition of In increased, while the phase fraction of Fcc(Cu) phase decreased. Moreover, the liquidus temperatures of Ag50.5Cu33.3Sn16.2-xInx alloys also decrease with increasing In content. In this work, the Ag-Cu-Sn-In quaternary thermodynamic database was ideally extrapolated from the published literature for Ag-Cu-Sn, Ag-Cu-In, Ag-Sn-In and Cu-Sn-In thermodynamic databases. The calculated vertical section of Ag50.5Cu33.3Sn16.2-Ag50.5Cu33.3In16.2 agreed generally with the phase transition temperatures measured in the present experiment. Finally, the solidification behaviors of Ag50.5Cu33.3Sn16.2-xInx as-cast alloys were analyzed by thermodynamic calculation of the Scheil–Gulliver non-equilibrium model. The simulated solidification processes of some Ag50.5Cu33.3Sn16.2-xInx alloys are, in general, consistent with the experimental results in the present work, which would provide a theoretical basis for the design of novel Ag-Cu-Sn-In brazing alloys.